Free kick designing an interactive website for the Davao Football Association - Homez, Maureen Joyce Filipinas
Websites give organizations the freedom to update their customers with new information without the need for face-to-face communication. In order for it to be effective, it should attract customers to use the website. This thesis production focused on interactivity as the main feature of designing the Davao Football Association (DFA) website. The researcher was able to create an interactive design based on her critique of the current DFA website with the use of the different design principles